Fiscal competition in space and time: An endogenous-growth approach - Daniel Thomas Becker; Michael Rauscher (Universität Rostock, Institut für Volkswirtschaftslehre, 2007)
Is tax competition good for economic growth? The paper addresses this question by means of a simple model of endogenous growth. There are many small jurisdictions in a large federation and individual governments benevolently maximise the welfare of immobile residents. Investment is costly: Quadratic installation and de-installation costs limit the mobility of capital. The paper looks at optimal taxation and long-run growth. In particular, the effects of variations in the cost parameter on economic growth and taxation are considered. It is shown that balanced endogenous growth paths do not always exist, that, if they exist, the economic growth rate is positively related to the mobility of capital, that the impact of the mobility prameter on the tax rate is ambiguous and that the tax rate may go to zero even if mobility costs are strictly positive.
Keywords: H70; F21; O00; 330; Fiscal Federalism; Tax Competition; Endogenous Growth; Steuerwettbewerb; Neue Wachstumstheorie; Optimale Besteuerung; Gleichgewichtiges Wachstum; Direktinvestition